Particular features of osteopenic syndrome in patients with type 1 diabetes mellitus - O. S. Tonkikh; V. D. Zavadovskaya; Ye. B. Kravets; O. Yu. Kilina; O. S. Shoulga; O. P. Zorkaltseva (Бюллетень сибирской медицины, 2008)
In this article the results of ultrasound osteometry in patients with type 1 diabetes mellitus are discussed. The aim of the research was to estimate the index of bone mineral density in adult patients considering the severity, duration of the disease, age of the onset of the disease, sex, age and body weight of the patients. The leading factors which influence bone mineral density in patients with type 1 diabetes mellitus are determined.